식품의약품안전청의 의약품안전사용정보방 웹사이트 구축을 위한 컨텐츠 개발 - 지은희(Eunhee Ji); 박효영(Hyo Yung Park); 노혜진(Hyejin Noh); 이동은(Dong Eun Lee); 한나영(Nayoung Han); 정소현(Sohyun Jeong); 김인화(In-Wha Kim); 신완균(Wan Gyoon Shin); 오정미(Jung Mi Oh) (Yaghag-hoi-ji, 2012)
The purpose of this study was to construct database for a drug safety information website to serve as an access point of up-to-date resources for a wide variety of drug-safety information helping patients and healthcare professionals make well-informed decisions about medication use. All the contents developed were confirmed by the council of advisors who were the experts in drug safety. The detailed contents of database on frequently prescribed drug including 9 NSAIDs, 19 antibiotics, 24 cardiovascular, 21 metabolic, 14 respiratory, 20 digestive, 22 hormonal, 10 genitourinary, 10 anti-allergic, 27 antifungal/antiviral, and 71 neuropsychiatric agents were developed based on the approved drug labeling of the Korean FDA. A separately searchable database of drug-specific safety information for patients and health professionals was constructed for users in need of different depth of knowledge on using medications safely. The safety information on highly prevalent chronic diseases and drug classes was also developed. Finally the most recent global drug safety news was provided. The consumer directed information was developed in layman's terms as means of proving user-friendly information. The creation of this type of website is part of the Korean FDA's ongoing initiative to address and promote the safe use of medications for the public.